Impacts of the Affordable Care Act on Receipt of Women's Preventive Services in Community Health Centers in Medicaid Expansion and Nonexpansion States. Issue 2 (February 2021) - Hatch, Brigit; Hoopes, Megan; Darney, Blair G.; Marino, Miguel; Templeton, Anna Rose; Schmidt, Teresa; Cottrell, Erika
Abstract : (Abstracted from Womens Health Issues 2021;31:9–16) After implementation of insurance expansion provisions under the Affordable Care Act (ACA), rates of health insurance coverage increased dramatically throughout the United States in 2014 and improved care delivery for some services. Despite the availability of federally funded Medicaid expansion to all states, many did not accept ACA-sponsored expansion and opted to maintain current eligibility criteria in their states.